MENINGKATKAN PERAN ORANGTUA DALAM MEMBIMBING ANAK BELAJAR DI RUMAH - Yunia Nurholishoh (STKIP Subang, 2022)
In order to provide information that can be used to improve parental assistance to children, the purpose of this study was to determine the extent to which parents help students study at home. Parents have received many complaints about the prolonged absence of their children since the pandemic. This study uses a qualitative descriptive approach and a non-engaged observation method by observing parents' home-based learning assistance activities without telling children that they are being recorded. The second method conducted five-question structured interviews with parent representatives for each grade level (grades 1, 2, 3, 4, 5, and 6). The study shows that the role of parents in educating their children to study at home is irreplaceable. Parents need to motivate, instill confidence and show compassion for their children to overcome the challenges they face in school. This will affect not only the learning process but also the children's self-confidence, problem-solving skills, independence, and emotional stability. The study found that almost all parents are supportive of their children's learning, but they need to learn how to help their children learn so that everyone can learn comfortably.